The Breviarum ab urbe condita of Eutropius : the right honourable secretary of state for general petitions : dedicated to Lord Valens, Gothicus Maximus & perpetual emperor - Eutropius, činný 4. století (Translated texts for historians ;, 1993)
The first full-scale translation and commentary on Eutropius, whose Breviarium (Abbreviated History of Rome) was a major vehicle for transmitting knowledge of Roman history to people of the Middle Ages and beyond.